Inflammation, the stress response system and the kynurenine pathway in the pathogenesis of depression and response to ECT - Hughes, Martina M. (Trinity College (Dublin, Ireland). Department of Physiology, 2014)
Major depression is a serious psychiatric disorder and a leading source of disability worldwide. However, the precise biological basis of depression remains elusive. Evidence suggests that activation of the inflammatory response system may have a pivotal role to play in the pathogenesis of certain subtypes of depression. Patients with severe treatment-resistant depression or with a history of childhood trauma are often characterised by a pro-inflammatory phenotype. In accordance with this, in this thesis, assessment of the circulating inflammatory profile in a cross-sectional cohort of severely depressed patients and additionally, in an independent cohort of severely depressed patients referred for ECT, revealed that both cohorts of depressed patients were characterised by increased circulating concentrations of the inflammatory cytokine IL-6 and the acute phase protein, C-reactive protein (CRP).
Keywords: Physiology, Ph.D.; Ph.D. Trinity College Dublin